1996
DOI: 10.1128/iai.64.8.3294-3300.1996
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Shiga toxin across polarized intestinal cells in tissue culture

Abstract: Escherichia coli strains producing Shiga toxins (Stx) 1 and 2 colonize the lower gastrointestinal tract in humans and are associated with gastrointestinal and systemic diseases. Stx are detectable in the feces of infected patients, and it is likely that toxin passes from the intestinal tract lumen to underlying tissues. The objective of this study was to develop an in vitro model to study the passage of Stx across intact, polarized cell monolayers. Translocation of biologically active Stx was examined in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 35 publications
3
59
0
1
Order By: Relevance
“…Interestingly, uptake of Stx1 was faster by T84 than by Caco‐2 cells. This is in agreement with previous studies showing that Gb3 expression has an inhibiting effect on Stx1 translocation across polarized epithelial monolayers (Acheson et al ., 1996). These findings might suggest the existence of different receptors for Stx transport across intestinal cells and for induction of cell death on target cells.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, uptake of Stx1 was faster by T84 than by Caco‐2 cells. This is in agreement with previous studies showing that Gb3 expression has an inhibiting effect on Stx1 translocation across polarized epithelial monolayers (Acheson et al ., 1996). These findings might suggest the existence of different receptors for Stx transport across intestinal cells and for induction of cell death on target cells.…”
Section: Discussionsupporting
confidence: 94%
“…In humans, transcytosis of VT thus triggers cytotoxicity and inflammation, both of which are important in precipitating disease. Increasing levels of Gb3 on intestinal epithelial cells leads to diminished trans-cellular movement of VT (Acheson et al, 1996). We therefore propose that expression of Gb3 by crypt epithelial cells of the small and large intestine in cattle occludes translocation of VT which, combined with the receptor isoform(s) and organization on these cells, leads to an absence of local or systemic cytotoxicity or inflammation in the bovine host.…”
Section: Discussionmentioning
confidence: 95%
“…Damage to the intestinal epithelium by Shiga toxin, or other in£ammatory mediators, may aid translocation of the toxin to the bloodstream (Paton and Paton 1998b); gaps between cells may be a further pathway. However, Acheson et al (1996) have demonstrated that toxin can move through intact epithelial cells and this may be an additional transport mechanism allowing toxin to reach extraintestinal sites. Although both Stx1 and 2 are thought to cause direct damage to human glomerular cells, there is increasing evidence that cytokines such as interleukins and tumour necrosis factor in association with bacterial LPS may be involved in the process.…”
Section: Shiga T Oxinsmentioning
confidence: 99%